Swimming with Sharks: Technology Ventures, Defense Mechanisms and Corporate Relationships - Katila, Riitta; Rosenberger, Jeff D.; Eisenhardt, Kathleen M. (Administrative Science Quarterly, 2008)
This paper focuses on the tension that firms face between the need for resources from partners and the potentially damaging misappropriation of their own resources by corporate “sharks.” Taking an entrepreneurial lens, we study this tension at tie formation in corporate investment relationships in five U.S. technology-based industries over a 25-year period. Central to our study is the “sharks” dilemma: when do entrepreneurs choose partners with high potential for misappropriation over less risky partners? Our findings show that entrepreneurs take the risk when they need resources that established firms uniquely provide (i.e., financial and manufacturing) and when they have effective defense mechanisms to protect their own resources (i.e., secrecy and timing). Overall, the findings show that tie formation is a negotiation that depends on resource needs, defense mechanisms, and alternative partners. These findings contribute to the recent renaissance of resource dependence theory and to the discussion on the surprising power of entrepreneurial firms in resource mobilization.